Development and in vitro evaluation of colonic drug delivery systems for tegaserod maleate - Venkatesh, D Nagasamy; Reddy, Ajay Kumar; Samanta, M K; Suresh, B (Asian Journal of Pharmaceutics (AJP), 2014)
Interest exists in developing site-specific systems of release of drug in the colon via the oral route. Tegaserod maleate was used as a drug for irritable bowel syndrome, whereas Eudragit L 100 and S100 mixture (1:1, 1:2, and 1:3) were used as pH-sensitive polymers. Various approaches, namely microcapsules, compressed microcapsules, and modified tablets were made for this study. The microcapsules were prepared by the emulsion–solvent evaporation method using drug and mixture of polymers. The prepared microcapsules were evaluated for various physicochemical parameters such as particle size, surface morphology, drug loading capacity, and in vitro dissolution studies by half-dilution method employing various pH environments (pH 1.2–6.8) for 24 hours. The batch prepared using the 1:2 drug polymer ratio was selected as an ideal batch for compression to get the compressed tablet of the microcapsules. The compressed microcapsules were evaluated for physicochemical parameters such as average weight, hardness, friability, thickness, and in vitro dissolution by the halfdilutionmethod. The modified tablets were also prepared using the drug with hydroxylpropylmethylcellulose as the inner material and ethyl cellulose as the outer material employing the double compression technique. The prepared tablets were subjected to various physicochemical parameters, including thickness, weight variation test, drug content, hardness, friability, and in vitro dissolution study using the half-dilution method (pH 1:2–6.8) for 24 hours. Comparisons of microcapsules, compressed microcapsules, and modified tablets containing tegaserod maleate indicated that the drug release profiles from the microcapsules were found to be better than the compressed microcapsules and the modified tablets in the colonic environment.